1976
DOI: 10.2307/1128447
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in the Development of Formal Reasoning

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…299) suggested 30 years ago, the solution of the TOH problem requires the person's bcognizance of actions or of coordinationsQ (i.e., inductive reasoning); whereas, emerging formal operational thought allows these past actions to be incorporated into a generalized model of problem solving through breflexive abstractionQ (i.e., deductive reasoning). Furthermore, these findings are congruent with the studies reviewed earlier that also identified some association between formal operational reasoning and cognitive processes related to executive function and/or prefrontal function (Cloutier & Goldschmid, 1976;Hooper et al, 1985;Shute & Huertas, 1990;Taylor, 1998).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…299) suggested 30 years ago, the solution of the TOH problem requires the person's bcognizance of actions or of coordinationsQ (i.e., inductive reasoning); whereas, emerging formal operational thought allows these past actions to be incorporated into a generalized model of problem solving through breflexive abstractionQ (i.e., deductive reasoning). Furthermore, these findings are congruent with the studies reviewed earlier that also identified some association between formal operational reasoning and cognitive processes related to executive function and/or prefrontal function (Cloutier & Goldschmid, 1976;Hooper et al, 1985;Shute & Huertas, 1990;Taylor, 1998).…”
Section: Discussionsupporting
confidence: 90%
“…Davis (1987) found that there were broad differences in attainment and maintenance of formal operational reasoning between Western and non-Western communities. With regard to a cognitive process explanation, Cloutier and Goldschmid (1976) found that proportional reasoning, the first sub-stage of formal operational thought, correlated with nonverbal capacity and IQ.…”
Section: Introductionmentioning
confidence: 99%
“…Formal reasoning is consistently related to the Rod and Frame test and frequently related to tests associated with general ability. These findings are consistent with Cloutier and Goldschmid (1976) and place formal as a mix between traditional school learning and strategy utilization.…”
Section: Discussionsupporting
confidence: 83%
“…A number of researchers suggest that formal reasoning is closely related to achievement and to general ability (Cloutier & Goldschmid, 1976;Keating, 1976;Yudin, 1966). For example, Cloutier and Goldschmid found that Raven's matrices correlated 0.46 with proportional reasoning, and verbal ability correlated 0.34.…”
Section: Correlates Of Formal Measuresmentioning
confidence: 99%
“…These findings were supported in a number of studies (e.g. Lovell, 1961 ;Lunzer, 1965;Noelting et al, 1973;Noelting, 1975, Brainerd, 1971, although some individual and age differences have been reported (Davies, 1965;Yost, Siegel and Andrews, 1962;Goldberg, 1966;Fishbein, Pampu and Manz~t, 1970;Cloutier and Goldschmid, 1976). …”
Section: Introductionmentioning
confidence: 61%